THE EFFECT OF THE MATHEMATICAL SKILLS ACQUIRED IN WOODWORK ON STUDENTS’ ACHIEVEMENT IN MATHEMATICS - Kimiti, Richard P.; Waweru, Samuel N.; Mulwa, David M.; Muema, Elizabeth N.; Kituka, Titus M. (My University, 2011)
Economic status of students, gender and family size have been found to affect students’ achievement in mathematics. However, there seems to be limited research on the effects of knowledge and affective skills acquired from other subjects on students’ achievement in mathematics. The research objectives of the study were to determine whether the cognitive and practical skills acquired in woodwork affects students’ achievement in mathematics. The study also sought to find out whether the learning of similar topics in woodwork affected students’ achievement in mathematics. The research methodology applied was ex-post facto design. The study was carried out in four secondary schools which offered woodwork in Machakos County, Kenya and involved a student sample of 158. Data was collected by use of three mathematics tests and a questionnaire for woodwork students. The results revealed that cognitive and practical skills acquired in woodwork have a positive effect on students’ achievement in mathematics. The learning of similar topics in woodwork and mathematics has a positive effect on students’ achievement in mathematics.
Keywords: Cognitive skills; Practical skills; Students’ achievement